Age distribution of breast cancer from a Thailand population-based cancer registry - Manas Kotepui (2018)
Background: Breast cancer is a common cancer worldwide. With the establishment of Thailand's populationbased cancer registry and availability of complete data from 2002-2011, it is of interest to investigate the epidemiologic and clinic-pathological profiles of breast cancer based on the population-based registry data. Methods: The data of all breast cancer patients in the registry for the period of 2002-2011 were included. All medical records of the patients diagnosed from documents of National Cancer Registry of Thailand were retrieved and the following information abstracted: age, clinical characteristics, and histological variables. Thailand census data for the period of 2002-2011 were used to provide the general population's statistics on age, gender, and other related demographic factors. Results: Over the 10 year-period, 7,711 breast cancer cases were included. The disease incidence under age 40 years was relatively low (4.13/105) while the incidence in the age groups 40 and older was very high (39.2/105). The vast majority of breast cancer cases (88.8%) were diagnosed by histology as primary lesions in the breast. The most common of patients with breast cancer (36.4%) had regional lymph node involvement and the most common of histopathology diagnosed in patients (84.2%) was an infiltrating duct carcinoma. Conclusions: This study showed a high incidence of breast cancer in older subjects, and high rate of breast cancer in Thailand. Future studies should explore clinical and molecular disease patterns.